Ingresos y egresos del Gobierno Autónomo Descentralizado Municipal del Cantón San Francisco de Puebloviejo en el período 2021-2022. - Abril Poveda, Britney Anais (2024)
Income and Expenses of the Municipal Decentralized Autonomous Government of the Canton of San Francisco de Puebloviejo in the Period 2021-2022 is the topic that will be discussed in this case study, it is carried out with the purpose of knowing a little more in depth about the management that This institution carries out these accounts, applying the line of research “Tax Financial Management and Social Commitment”, in addition to the percentage indicator that will help us to know the variations that are generated between the different periods mentioned above. The method we will use will be analytical-descriptive and qualitative-quantitative. Since these methods will help us interpret the results that will be obtained during the development of this project. During its development, the main income and expense accounts that the institution has and how they manage their income and expenses were observed with the aim of obtaining key information to support the financial decisions of the directors. These decisions provide a complete vision of the economic and administrative reality of the company.